THE MOUNTING OF THE NEW 2-M RCC TELESCOPE AT TERSKOL IN 1994-1996 - Anatsky, V. A.; Karpov, N. V.; Kuznetcov, V. L.; Sergeev, A. V.; Tarady, V. K.; Fomenko, A. A. (Одеські астрономічні публікації, 2017)
In 1996 "Carl Zeiss Jena" and Centre of Astronomical and Medico-Ecological Investigations had mounted new 2-m RCC telescope, named as ZTT (Zerkalny Telescop v Terskole). The general review of the telescopes and buildings on the hiltop Terskol (3100m) are given. The basic design of ZTT are described. The results of first engineering tests of the new 2-m RCC telescope have been discussed.